1993
DOI: 10.1016/0044-8486(93)90445-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of commercial enrichment diets on the nutritional value of the rotifer (Brachionus plicatilis)

Abstract: The rotifer, Brachionus plicatilis, pre-fed on baker's yeast, was enriched for 6 h with three commercial products from Artemia Systems S.A., namely Protein Selco (microcapsules), Dry Selco (microparticles) and Super Selco (an emulsion containing high levels of n-3 HUFA). The biochemical composition (protein, carbohydrate, total lipid, lipid classes and fatty acids) and dry weight of the rotifers before and after the enrichment experiments were studied. Two of the enrichers, Dry Selco and Super Selco, are rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 31 publications
5
35
0
1
Order By: Relevance
“…In contrast, Artemia nauplii, and especially nauplii of Artemia franciscana, which is the common strain used in the aquaculture, contain markedly lower levels of FAAs compared with wild copepods (Fyhn et al 1993;Helland 1995) and is unstable under starving conditions. On the other hand, the nutritional quality of the rotifer Brachionus plicatilis has been studied by many authors (Fernandez-Reiriz et al 1993;Caric et al 1993;Fielder et al 2000). These studies revealed that fish larvae fed on rotifers often exhibit slow growth rates and high mortalities, which has been attributed to PUFA deficiencies and the biochemical changes observed in the nutritional value of Brachionus plicatilis.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, Artemia nauplii, and especially nauplii of Artemia franciscana, which is the common strain used in the aquaculture, contain markedly lower levels of FAAs compared with wild copepods (Fyhn et al 1993;Helland 1995) and is unstable under starving conditions. On the other hand, the nutritional quality of the rotifer Brachionus plicatilis has been studied by many authors (Fernandez-Reiriz et al 1993;Caric et al 1993;Fielder et al 2000). These studies revealed that fish larvae fed on rotifers often exhibit slow growth rates and high mortalities, which has been attributed to PUFA deficiencies and the biochemical changes observed in the nutritional value of Brachionus plicatilis.…”
Section: Introductionmentioning
confidence: 97%
“…However, they can be deficient in Eicosapentaenoic Acid (EPA, 20:5n-3), although most common Artemia strains used have a relatively high content of EPA [7,14,26]. Both rotifers and Artemia nauplii naturally lack, or have insignificant quantities of, Docosahexaenoic Acid (DHA, 22:6n-3) and are rich in linolenic acid (18:3n-3) and, to a lesser extent, linoleic acid (18:2n-6) [27,28]. Furthermore, the presence of high amounts of 18:3n-3 suppresses the conversion of EPA to DHA.…”
Section: Advantages and Disadvantages Of Different Live Preysmentioning
confidence: 99%
“…Furthermore, the presence of high amounts of 18:3n-3 suppresses the conversion of EPA to DHA. Since failure to provide correct essential fatty acids is a primary cause of unsuccessful culture [29], it is common practice to enrich rotifers and Artemia with essential fatty acids [7,27,30,31]. Enrichment consists in feeding an enrichment product rich in the desired essential fatty acids to filter-feeding Artemia and rotifers.…”
Section: Advantages and Disadvantages Of Different Live Preysmentioning
confidence: 99%
“…Each flask was gently aerated by a glass pipette at a temperature of 18 ± 0.5 0 C. Six counts of 50μL were then taken to estimate the initial number of the rotifers per flask. These counts continued during the experiment in order to estimate the survival rate of the animals and the possible on a lipid-rich diet (Fernandez-Reiriz et al, 1993;Naz, 2008;Demir and Diken, 2011a,b;Maehre et al, 2013). Brachionus plicatilis are commonly raised on baker's yeast, which does not supply adequate levels of ω-3 polyunsaturated fatty acids (PUFA).…”
Section: Feeding Trialmentioning
confidence: 99%